Developing Codes to Capture Post-Operative Care - Mehrotra, Ateev (RAND Corporation, 2016)
This report makes recommendations to the Centers for Medicare & Medicaid Services on a set of nonpayment codes that can be used to collect information on the number and level of post-operative visits. The proposed nonpayment codes aim to capture the major differences in the breadth and intensity of post-operative care provided to Medicare beneficiaries.